1963
DOI: 10.1044/jshr.0604.315
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Measurements at the Eardrum as an Aid to Diagnosis

Abstract: The clinical measurement of acoustic impedance at the eardrum is described. Significant modifications of the traditional Schuster bridge by Zwislocki led to the development of an acoustic impedance bridge that permits a sufficiently reliable and rapid determination of absolute acoustic impedance. The results of clinical investigation with this instrument demonstrate the value of the acoustic method in the evaluation of the status of the middle ear mechanism. The presence of conductive hearing losses due to var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1965
1965
2000
2000

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…5 A higher probe-tone frequency (such as 600 or 800 Hz) may yield a W-shaped tympanogram or an undulating tympanogram, even in persons with unequi vocal l y normal hearing. 4 These t ym-CONTEMPORARY TYMPANOMETRY-HALL panograms are sometimes classified as types D and E. 5…”
Section: Tympanogram Classificationmentioning
confidence: 99%
“…5 A higher probe-tone frequency (such as 600 or 800 Hz) may yield a W-shaped tympanogram or an undulating tympanogram, even in persons with unequi vocal l y normal hearing. 4 These t ym-CONTEMPORARY TYMPANOMETRY-HALL panograms are sometimes classified as types D and E. 5…”
Section: Tympanogram Classificationmentioning
confidence: 99%
“…Feldman (76), using the Zwislocki acoustic-impedance bridge, has shown that otosclerotics have smaller compliance values than normals. He describes a new instrument for measuring acoustic impedance based on the principle of Schuster's acoustic bridge.…”
Section: Abnormalities Of Hearingmentioning
confidence: 99%
“…Feldman 61 points out the value of acoustic impedance measures after stapes surgery to detect the condition of the prosthesis. The compliance is usually somewhat larger than normal with a prosthesis and will be considerably larger if the prosthesis has become dislodged.…”
Section: Absolute Impedance Measuresmentioning
confidence: 99%